Structuring Reality So That the Law Will Follow: British Columbia Teachers’ Quest for Collective Bargaining Rights - Slinn, Sara (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2011)
Abstract The British Columbia Teachers’ Federation (bctf), representing all public elementary and secondary school teachers in the province, is one of the largest and most powerful unions in British Columbia. bctf has always sought formal rights to full-scope collective bargaining, and unrestricted access to striking at the school board level. It has employed a sustained, sophisticated series of strategies to achieve these objectives, quickly adapting to changing political and legal environments. The bctf has had significant success in advancing its labour relations agenda, establishing a diﬀerent trajectory for teachers than for most public sector workers in Canada. This article maps bctf’s labour relations strategies and agenda against the backdrop of the political and legal environments, from bctf’s inception to present-day. It argues that, as a result of these factors, BC teachers have experienced a different labour relations history than most public sector workers. Drawing on and adapting Rose’s (2004) eras of public sector labour relations, this article identifies the following eras of BC teacher labour relations: an era of exclusion (to 1982); resistance and revitalization (1982-86); expansion (1987-93); reform (1994); reprieve (1994-2001); restraint and consolidation (2002-2007); and reaching an era of realignment beginning in 2007.